Succession Analysis in Family Business (Case Study at PT. BJE) - OH, Retno Sri Wahyuningsih; Agatha Ferijani (Journal of Management and Business Environment (JMBE), 2021)
This study aims to analyze the family business succession process carried out by PT. BJE in the election of son-in-law as the business successor. To understand the selection process, a succession analysis was carried out through the seven stages of the Seven-Point Star Model. The research method uses descriptive qualitative with a case study phenomenology approach. This study used primary and secondary data obtained by means of semi-structured in-depth interviews, participatory observation, and company documentation. The results showed that the stages of the Seven-Point Star Model succession planning had not yet been fully implemented by PT. BJE.